Humornost v kratki pripovedi Prežihovega Voranca - Jesenšek, Marko (Jezik in slovstvo, 2010)
The discussion presents the linguistic characteristics of humour in the story Tadej pl. Spobijan. In it Prežihov Voranc presents a witty and humorous account of a meeting between middle class social outcasts and people from various social strata, thus demonstrating that he has a sense of humour despite the fact that we are not able to label him as a humorist writer. The humour is evident in the superb linguistic and stylistic illustration of the social conditions in which the individuals find themselves, while this is linguistically supplemented with folk expression and metaphor, words with figurative meaning and interesting word games, as well as with witty remarks, personifications and renaming. In his short story humour is concealed in naturalist, expressionist and realist narrative, in descriptions or short dialogues in which humour interweaves with irony and satire, sometimes concluding in grotesque images and misshapen emotions.
Keywords: Prežihov, Voranc; Slovene literature; slovenska književnost; short story; metaphor; kratka pripoved; linguistic characteristics; metaforika; jezikovne značilnosti; stylistic characteristics; slogovne značilnosti; humour; humor; satire; irony; satira; ironija; grotesque; groteska